Recent Developments in Alpine Tourism: A Life Cycle Approach - Tuppen, John (Turyzm/Tourism, 2002)
The article presents recent trends in the tourist economy in the Alpine region. With reference to the development cycle of the tourist product, proposed by Butler, the author claims that the Alpine tourist centres have already reached the maturity stage. Their further development requires active intervention in order to refresh the tourist product. Further in the article, a variety of tourist development strategies have been presented, which might improve the poor condition of many tourist centres in the region under discussion.